World Health Organization‐defined eosinophilic disorders: 2022 update on diagnosis, risk stratification, and management. Issue 1 (8th October 2021) - Shomali, William; Gotlib, Jason
Abstract: Disease Overview: The eosinophilias encompass a broad range of nonhematologic (secondary or reactive) and hematologic (primary or clonal) disorders with potential for end‐organ damage. Diagnosis: Hypereosinophilia (HE) has generally been defined as a peripheral blood eosinophil count greater than 1.5 × 10 9 /L. After exclusion of secondary causes of eosinophilia, diagnostic evaluation of primary eosinophilias relies on morphologic review of the blood and marrow, standard cytogenetics, fluorescence in situ hybridization, next generation sequencing gene assays, and flow immunophenotyping to detect histopathologic or clonal evidence for an acute or chronic hematolymphoid neoplasm. Risk Stratification: Disease prognosis relies on identifying the subtype of eosinophilia. After evaluation of secondary causes of eosinophilia, the 2016 World Health Organization endorses a semi‐molecular classification scheme of disease subtypes. This includes the major category "myeloid/lymphoid neoplasms with eosinophilia and rearrangement of PDGFRA, PDGFRB, or FGFR1 or with PCM1‐JAK2 ", and the myeloproliferative neoplasm subtype, "chronic eosinophilic leukemia, not otherwise specified" (CEL, NOS). Lymphocyte‐variant HE is an aberrant T‐cell clone‐driven reactive eosinophila, and idiopathic hypereosinophilic syndrome (HES) is a diagnosis of exclusion. Risk‐adapted Therapy: The goal of therapy is to mitigate eosinophil‐mediated organ damage. For patients with milder forms of eosinophilia (eg, < 1.5 × 10 9 /L) without symptoms or signs of organ involvement, a watch and wait approach with close follow‐up may be undertaken. Identification of rearranged PDGFRA or PDGFRB is critical because of the exquisite responsiveness of these diseases to imatinib. Corticosteroids are first‐line therapy for patients with lymphocyte‐variant HE and HES. Hydroxyurea and interferon‐α have demonstrated efficacy as initial treatment and in steroid‐refractory cases of HES. Mepolizumab, an interleukin‐5 (IL‐5) antagonist monoclonal antibody, was recently approved by the US Food and Drug Administration for patients with idiopathic HES. The use of the IL‐5 receptor antibody benralizumab, as well as other targeted therapies such as JAK2 and FGFR1 inhibitors, is under active investigation.